HUBUNGAN SEJENIS MENURUT PANDANGAN TOKOH MASYARAKAT DITINJAU DARI PERSPEKTIF HUKUM ISLAM (STUDY KASUS KELURAHAN PELAMUNAN KABUPATEN SERANG) - Mellia Lesthari (Relinesia: Jurnal Kajian Agama dan Multikulturalisme Indonesia, 2024)
Sex deviance develops over time, so that sex becomes a "dirty" and "disgusting" word, whereas in Quraish Shihab's view that sex in the Islamic view is something holy. Sex is a fundamental difference related to reproduction, in one type, which divides this breed into two parts, male and female according to the sperm (male) and egg (female) produced. The problem arises if then there is sexual deviance, namely similar relationships that occur among the community, including one of them in Pelamunan Village, Serang District.The formulation of the problem in this study is: How is the relationship similar according to the views of community leaders in Pelamunan village, Serang District, viewed from the perspective of Islamic law? and what are the factors causing the emergence of public figures' views on similar relationships in Pelamunan village, Serang District This study aims to determine similar relationships according to the views of community leaders in Pelamunan village, Serang District, from the perspective of Islamic law and to find out the factors causing the emergence of community leaders' views on similar relationships in Pelamunan village, Serang District. This research is included in field research, according to its nature this research is descriptive. The data collection methods used are interviews, observations and documentation. The results showed that, community leaders viewed the existence of same-sex enthusiasts as damaging the joints of people's lives should have received stricter action because it was feared that it could be transmitted to the younger generation in Pelamunan Village, this was due to same-sex behavior contrary to religious norms and violations of humanitarian law. The perpetrator is declared to be a person who deviates from reasonableness and needs to be treated seriously so as not to cause troubling social ills.